Unlocking the potential of integrated reporting in driving firm value - Minda Muliana Br Sebayang; Azhar Maksum; Warsani Purnama Sari (Journal of Innovation in Business and Economics, 2025)
This study analyzes the effect of corporate governance and accounting information quality on firm value, with integrated reporting quality as a mediating variable. The research was conducted using a quantitative approach with the WarpPLS statistical tool. The sample comprises 75 companies listed on the Indonesia and Malaysia stock exchanges. The results show that there is a difference in the effect of integrated reporting quality on firm value in Indonesia and Malaysia, with the integrated reporting implementation variable acting as a moderating factor. Good corporate governance is proven to influence the quality of integrated reporting. Additionally, accounting information quality positively and significantly affects firm value. It also positively and significantly affects the quality of integrated reporting. Furthermore, integrated reporting quality is shown to impact firm value. Good corporate governance affects firm value through integrated reporting quality. However, good corporate governance does not directly influence firm value, and accounting information quality does not significantly affect firm value through integrated reporting quality.